Evaluation of virtual environment as a form of interactive resuscitation exam. Issue 4 (2nd October 2017) - Leszczyński, Piotr; Charuta, Anna; Kołodziejczak, Barbara; Roszak, Magdalena
ABSTRACT: There is scientific evidence confirming the effectiveness of e-learning within resuscitation, however, there is not enough research on modern examination techniques within the scope. The aim of the pilot research is to compare the exam results in the field of Advanced Life Support in a traditional (paper) and interactive (computer) form as well as to evaluate satisfaction of the participants. A survey was conducted which meant to evaluate satisfaction of exam participants. Statistical analysis of the collected data was conducted at a significance level of α = 0.05 using STATISTICS v. 12. Final results of the traditional exam (67.5% ± 15.8%) differed significantly ( p  < 0.001) from the results of the interactive exam (53.3% ± 13.7%). However, comparing the number of students who did not pass the exam (passing point at 51%), no significant differences ( p  = 0.13) were observed between the two types exams. The feedback accuracy as well as the presence of well-prepared interactive questions could influence the evaluation of satisfaction of taking part in the electronic test. Significant differences between the results of a traditional test and the one supported by Computer Based Learning system showed the possibility of achieving a more detailed competence verification in the field of resuscitation thanks to interactive solutions. GRAPHICAL ABSTRACT: